Women ageing : social work intervention - Srivastava, Vinita (Jaipur : Rawat Publications, 2010)
Study with reference to older women in Girwa Tahsil of Rajasthan.
Includes bibliographical references (p. [269]-299) and index.
Keywords: Older women -- India -- Girwa (Tahsil) -- Social conditions; Older women -- India -- Girwa (Tahsil) -- Social conditions -- Statistics